Epstein–Barr Virus and Human Cytomegalovirus Infection in Intestinal Mucosa of Chinese Patients With Inflammatory Bowel Disease - Wang, Wei; Chen, Xin; Pan, Jie; Zhang, Xianhui; Zhang, Liyun (Frontiers in Microbiology, 2022)
Objective: This study aimed to determine the frequency of Epstein–Barr virus (EBV), cytomegalovirus (CMV) in mucosa and blood of inflammatory bowel disease (IBD) patients in China and evaluate their correlation with the clinical disease activities. Methods: Peripheral blood and endoscopic fresh colonic mucosal samples were collected from a cohort of 287 IBD patients and 50 controls. Viral DNA load was analyzed through quantitative real-time polymerase chain reaction. The clinical disease activity of ulcerative colitis (UC) and Crohn’s disease (CD) was assessed by the Mayo Clinic Score and Crohn’s disease activity index, respectively. Results: Among 287 IBD patients, 228 (79.4%) were positive for EBV and 99 (34.5%) were positive for CMV. EBV and CMV infection rates are significantly higher than those in the control group (28.0%, P<0.05; 4.0%, P<0.05). In addition, EBV/CMV prevalence increases as clinical activities progress (For EBV infection, the prevalence was 53.93% [48/89] in the mild group, 87.00% [87/100)] in the moderate group, and 94.90% [93/98] in the severe group; and for CMV infection, the prevalence was 3.37% [3/89] in the mild group, 27.00% [27/100] in the moderate group, and 70.41% [69/98] in the severe group). EBV and CMV loads are related to clinical disease activities (P<0.05). In addition, viral load in the intestinal mucosa of patients with acute exacerbation of IBD is higher than that of patients in remission. Conclusions: High prevalence of EBV and CMV is found in patients with IBD, and their prevalence is related to clinical disease activities. In addition, the viral load in the intestinal mucosa is associated with the status of mucosa in the same patients (active phase versus remission phase). Detection of viral load on mucosal specimens with quantitative real-time PCR is a feasible method to monitor EBV and CMV infection in IBD patients.